Analisis Faktor Yang Berhubungan Dengan Kejadian Sepsis Neonatorum Di Ruang Perinatologi Rsud Dr. H. Abdul Moeloek Provinsi Lampung - Yessy Rachmawati (Universitas Malahayati Lampung, 2021)
ABSTRACT: ANALYSIS OF FACTORS RELATING TO THE EVENT OF NEONATORUM SEPSIS IN THE PERINATOLOGY ROOM RSUD DR. H. ABDUL MOELOEK LAMPUNG PROVINCE IN 2020 Background : Maternal and child health problems are national problems that need to get top priority because they determine the quality of human resources in future generations. Children, especially infants, are more susceptible to diseases and unhealthy living conditions. Therefore, various efforts have been made by various parties to improve the health of infants, especially infants during the perinatal period (Ministry of Health Republic of Indonesia, 2018). Based on data from Dr. RSUD's medical records H. Abdul Moeloek from 2017 - 2019 saw an increase in the incidence of Neonatal sepsis in the Regional General Hospital (RSUD) Dr. H. Abdul Moeloek, where in 2017 there were 193 incidents, in 2018 there were 242 incidents and in 2019 there were 317 sepsis neonatorum incidents.Purpose : to find out the factors related to the occurrence of Sepsis Neonatorum in the Perinatology Room of RSUD Dr. H. Abdul Moeloek Lampung Province in 2020.Methods : This type of quantitative analytic research with a case control approach, the subjects in this study were all babies born in 2019 in RSUD Dr. H. Abdul Moeloek Lampung Province in 2020. The object of the study was the incidence of Sepsis Neonatorum, premature rupture of membranes, infection during pregnancy, LBW, and the sex of the baby. The research will be carried out after the proposal is approved.Research Result : It is known that out of 178 respondents, 144 (80.9%) of respondents did not have sepsis neonatorum, most of the respondents were 113 (63.5%) without PROM, most of the respondents had no infection as much as 158 (88.8%). Most of the respondents who were LBW were 99 (55.6%). There is a relationship between premature rupture of membranes and Sepsis Neonatorum in the Perinatology room of Dr. H. Abdul Moeloek, Lampung Province in 2020, (p value 0,000 OR 17,400) There is a relationship between infection during pregnancy and Sepsis Neonatorum in the Perinatology room of Dr. H. Abdul Moeloek, Lampung Province in 2020, (p value 0.001 OR 5,583). There is a relationship between LBW and Sepsis Neonatorum in the Perinatology room Dr. H. Abdul Moeloek, Lampung Province in 2020, (p value 0, 004OR 3.857). Suggestions for health workers to improve their capacity in providing health promotion regarding the treatment of Sepsis Neonatorum Keywords : Neonatal Sepsis, premature rupture of membranes, infection during pregnancy, LBW INTISARI: ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN SEPSIS NEONATORUM DI RUANG PERINATOLOGI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2020 Latar Belakang: Masalah kesehatan ibu dan anak merupakan masalah nasional yang perlu mendapat prioritas utama karena sangat menentukan kualitas sumber daya manusia pada generasi yang mendatang. Anak terutama bayi, lebih rentan terhadap penyakit dan kondisi hidup yang tidak sehat. Oleh sebab itu, dilakukan berbagai upaya oleh berbagai pihak untuk meningkatkan kesehatan bayi, terutama bayi pada masa perinatal (Kemenkes RI, 2018). Berdasarkan Data Rekam medis RSUD Dr. H. Abdul Moeloek dari tahun 2017 — 2019 terlihat peningkatan kejadian sepsis Neonatorum di Rumah Sakit Umum Daerah (RSUD) Dr. H. Abdul Moeloek, dimana tahun 2017 terdapat 193 kejadian, di tahun 2018 terdapat 242 kejadian dan di tahun 2019 terdapat 317 kejadian sepsis neonatorum.Tujuan Penelitian : untuk mengetahui faktor-faktor yang berhubungan dengan kejadian Sepsis Neonatorum di ruang Perinatologi RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2020.Metode Penelitian : Jenis penelitian analitik kuantitatif dengan pendekatan cros sectional, subjek dalam penelitian ini adalah seluruh bayi yang lahir di tahun 2019 di RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2020. Obyek dalam penelitian adalah kejadian Sepsis Neonatorum, ketuban pecah dini, infeksi saat hamil, BBLR, dan Jenis kelamin bayi. Penelitian akan dilaksanakan setelah proposal disetujui.Hasil Penelitian : Diketahui bahwa dari 178 responden, sebanyak 144 (80,9%) responden tidak Sepsis neonatorum, sebagian besar responden Tidak KPD sebanyak 113 (63,5%), sebagian besar responden tidak ada infeksi sebanyak 158 (88,8%). Sebagian besar responden BBLR sebanyak 99 (55,6%). Ada hubungan ketuban pecah dini (p value 0,000 OR 17,400) Ada hubungan infeksi (p value 0,001 OR 5,583). Ada hubungan BBLR (p value 0 ,004OR 3,857) dengan Sepsis Neonatorum di ruang Perinatologi RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2020. Saran tenaga kesehatan untuk meningkatkan kemampuan dalam pemberian promosi kesehatan mengenai penanganan Sepsis Neonatorum Kata kunci : Sepsis Neonatorum, ketuban pecah dini, infeksi saat hamil, BBLR